2004
DOI: 10.1124/mol.66.2.204
|View full text |Cite
|
Sign up to set email alerts
|

Defective Adult Neurogenesis in CB1 Cannabinoid Receptor Knockout Mice

Abstract: Pharmacological studies suggest a role for CB1 cannabinoid receptors (CB1R) in regulating neurogenesis in the adult brain. To investigate this possibility, we measured neurogenesis by intraperitoneal injection of bromodeoxyuridine (BrdU), which labels newborn neurons, in wild-type and CB1R-knockout (CB1R-KO) mice. CB1R-KO mice showed reductions in the number of BrdU-labeled cells to ϳ50% of wild-type (WT) levels in dentate gyrus and subventricular zone (SVZ), suggesting that CB1R activation promotes neurogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
199
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(224 citation statements)
references
References 43 publications
23
199
2
Order By: Relevance
“…First, the coincident expression of eCB synthesis enzymes and receptors in cortical progenitor zones demonstrates the existence of operational eCB signaling networks in neurogenic niches of the developing brain, where eCBs tune the rate of neural progenitor proliferation and the number of immature neurons committed to radial migration. Our findings indicate that eCB signaling is instrumental for embryonic neurogenesis, as also reported in adult brain (21), and data from knockout mice support a role for CB 1 Rs in committing SVZ progenitors to a pyramidal cell fate (10). Our in vitro morphometric and biochemical data also extend previous findings showing that both DAGL␣/␤ are recruited to elongating glutamatergic axons (9) with DAGL␣ being the primary enzyme concentrating in axonal growth cones.…”
Section: Discussionsupporting
confidence: 79%
“…First, the coincident expression of eCB synthesis enzymes and receptors in cortical progenitor zones demonstrates the existence of operational eCB signaling networks in neurogenic niches of the developing brain, where eCBs tune the rate of neural progenitor proliferation and the number of immature neurons committed to radial migration. Our findings indicate that eCB signaling is instrumental for embryonic neurogenesis, as also reported in adult brain (21), and data from knockout mice support a role for CB 1 Rs in committing SVZ progenitors to a pyramidal cell fate (10). Our in vitro morphometric and biochemical data also extend previous findings showing that both DAGL␣/␤ are recruited to elongating glutamatergic axons (9) with DAGL␣ being the primary enzyme concentrating in axonal growth cones.…”
Section: Discussionsupporting
confidence: 79%
“…It was shown that CB1 receptor activity is necessary for the upregulation of neurogenesis and proliferation after excitotoxic stress [220]. In good agreement with these findings, genetic deletion of CB1 receptors leads to defective neurogenesis [221]. The consequence of this effect on the learning phenotype is unclear but it is unrelated to the early loss of cognitive abilities in this strain [197].…”
Section: (D) Regulation Of Glial Activitysupporting
confidence: 70%
“…While GFAP/Gp120 Tg mice exhibited impaired neurogenesis and a decrease in cells with proliferating cell nuclear antigen (PCNA), administration of AM1241 to GFAP/Gp120 Tg mice resulted in enhanced in vivo neurogenesis in the hippocampus. An endogenous metabolite of docosahexaenoic acid and its derivatives (N-docosahexaenoylethanolamine and N-docosahexaenoylethanolamide) were shown to stimulate neurite growth, synaptogenesis, glutamatergic synaptic activity and neuronal differentiation of neural cells in hippocampal neurons [50,51]. Results of subsequent studies also confirmed the influence of the endocannabinoid system on neural progenitor cells (NCPs) regulation.…”
Section: Neurogenesis and Cannabinoidssupporting
confidence: 61%